The Empirical Impact of Leadership Style and Motivation on Employee Work Productivity: A Case Study of CV. Dian Persada Rotarindo in Mojokerto, East Java - Ulfah; R. Andy Oetario P; Bambang Eko Prabowo (Journal of Business and Behavioural Entrepreneurship, 2026)
This study examines the effects of Leadership Style and Motivation onProductivity. Using random sampling, data were collected from 132 respondents andanalyzed via simple linear regression using Minitab 15. The results show thatLeadership Style and Motivation simultaneously have a significant positive effect onProductivity ($f_{\text{value}} = 17.83 > f_{\text{table}} = 3.07$; $p = 0.000 < 0.05$).$H_0$ is rejected, and $H_a$ is accepted. However, both variables exhibit a weakrelationship correlation ($R = 0.466$) and account for only 21.7% of the variance inProductivity, while the remaining 78.3% is influenced by unexamined factors. Toenhance work productivity, organizations should focus on improving leadership andmotivation dimensions, specifically through integrity, fairness, socialization, anddiscipline.